(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Dinara L. Gajibalaeva (Rostov-on-Don, Russian Federation) Meals represent the so called structure of every day reality. Due to this the concept of meals, referring to a practical action is far from being explained. Being one of the basic forms of person’s every day life, meals are incorporated into many Chekhov’s fictional stories. As an element of fiction the situation of meals aquires cultural and simbólic significance , it turns to a sistem with its own code, thus requiring analysis. The article is an attempt to determine ontological and gnoseological peculiarities of the meals and the semantics of food on the basis of Chekhov’s stories. The parts of the text referring to the topic of meals and food itself, which allow to determine them as the elements of fictional and objective reality, filled with cultural content, are analyzed. Key words: the situation of meals, ontological peculiarities of the meals, gnoseological peculiarities of the meals, the semantics of food. DOI 10.23683/1995-0640-2018-3-119-124